Volume 2A: Turbomachinery 2018
DOI: 10.1115/gt2018-75008
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Stability Analysis of an Academic Rotor/Stator Cavity

Abstract: Self-sustained oscillations of rotor/stator cavity flows are well known to industry. This unsteady phenomenon can be very dangerous and jeopardize the structural integrity of aeronautical engines by damaging turbomachinery components or turbopumps in the context of space applications. Today, the origin of such flow instability and resulting limit-cycle is not well understood and still difficult to predict numerically. In order to have more insight of this phenomenon dynamic, an academic rotor/stator cavity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This numerical study also confirmed the capability of Computational Fluid Dynamic (CFD) to capture the annular and spirals structures as observed by Schouveiler (2001). Recently, studies [Bridel-Bertomeu (2016), Queguineur et al (2018)] relying on LES [Sagaut (2002)] and Dynamical Mode Decomposition (DMD) [Schmid (2010)] as well as linear stability analyses allowed a deeper investigation of the trigger of global modes in such systems. In this case, Bridel-Bertomeu (2016) used a local stability approach to locate the wavemaker of each reported mode.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…This numerical study also confirmed the capability of Computational Fluid Dynamic (CFD) to capture the annular and spirals structures as observed by Schouveiler (2001). Recently, studies [Bridel-Bertomeu (2016), Queguineur et al (2018)] relying on LES [Sagaut (2002)] and Dynamical Mode Decomposition (DMD) [Schmid (2010)] as well as linear stability analyses allowed a deeper investigation of the trigger of global modes in such systems. In this case, Bridel-Bertomeu (2016) used a local stability approach to locate the wavemaker of each reported mode.…”
Section: Introductionsupporting
confidence: 72%
“…1. First, the mean flow issued by a Large Eddy Simulation (LES) of the cavity [Bridel-Bertomeu (2016), Queguineur et al (2018)] is used to conduct the global stability analysis. To do so, the code GIFIE developed by Bridel-Bertomeu ( 2016) is used to solve the eigenvalues problem of Eq.…”
Section: Results Ans Discussionmentioning
confidence: 99%
See 1 more Smart Citation